ROLE OF SOCIAL MEDIA IN THE GOVERNMENT COMMUNICATION - Mirlina, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Nowadays the role of social media as a communication tool is increasing. Information technologies and communication habits of society changes also the way and the form how to create communication between the government and the society in Latvia. The aim of this research study is to evaluate the role of social media in Latvian government communication by analysing the use of the social media and interaction with the public. The formation of relations between government institutions and the society is defined in different policy documents of the Latvian government. Such research methods as document analysis, content analysis and comparative analysis to measure Latvian government profiles and followers’ involvement were employed to determine how social media use contributes to co-operation between the government and the public and effective exchange of information and coordination. The ways of communication in state administration performance have been changed. It is possible to mark two important changes – firstly, the government communication goal is not just to increase public awareness, but also interaction and involvement of the public in state administration, and secondly, development of information technology and public communication habits expands and makes varied methods and forms of government communication. Different Latvian government policy documents increase the role of communication in state administration, but the communication which is implemented by Latvian state institutions is unable to overcome public distancing and the lack of interest in the state administration.